Pengembangan Minat dan Bakat Siswa Melalui Pelatihan Public Speaking, E-Sport, dan Pembuatan Film Pendek di SMA Negeri 1 Kuta Selatan - Albert Fernando; Ida Ayu Lalita Rathintara; Agus Yudi Wiputra; Komang Hari Santhi Dewi; Anak Agung Raka Jayaningsih; I Putu Gede Abdi Sudiatmika (WIDYABHAKTI Jurnal Ilmiah Populer, 2022)
The service partner this time is Senior High School 1 Kuta Selatan which is located on Ketut Jetung Road, Kutuh, South Kuta District, Badung Regency, Bali. The partner's problem is that the development of students' interests and talents in the field of Public Speaking, E-Sports, and films are not yet optimal. In addition, the partners also do not have several extracurriculars that are able to help develop their abilities. Based on the partner's situation, training and self-development are needed in the field of Public Speaking, E-Sports, and films. This activity is carried out using the training method. The number of participants involved was 76 people. The stages of implementing the activities include preparation, implementation, evaluation, and reflection. The results of this program show that 87% of participants have abilities in the very good category. In this community service activity, all participants gave a positive response and hoped that this activity could be carried out continuously.